Infrared temperature measurement for condition monitoring of electrical machines - Tan, Edwin Ze Ming (2018)
Electrical machines and equipment have wide spread applications in both domestic and industrial sectors. To reduce the probability of unexpected breakdowns and preventing further damage done to these machines and equipment during a possible breakdown, health monitoring is of utmost importance and crucial in critical industrial applications. There are many ways to measure the temperature of the object. Some conventional methods of measuring temperature uses thermocouples, Resistance Temperature Detectors (RTDs) and thermistors. Despite having all these other choices, this project will look into the reasons why Infrared (IR) temperature sensor was chosen as the preferred temperature sensor.[9] IR temperature sensors for condition monitoring has gained attention in recent years. With the advent of affordable IR temperature sensors, thermography is emerging as a promising temperature monitoring method for electrical machines as they are non-invasive and noncontact.[5] IR temperature sensors are increasingly used to measure hot, out-of-reach objects, or areas where contact sensors could not be placed, such as on moving or rotating objects [3]. This project aims to implement an array of sensors, mounted onto a circular frame, along the inner wall of an electrical winding. Data obtained from the IR sensors will be transferred over to the computer to be stored and analysed.[9] [11]